Polyethyleneimine modified activated carbon for high-efficiency adsorption of copper ion from simulated wastewater - Jingming Lan; Baoying Wang; Bolin Gong (Water Science and Technology, 2022)
In this study, activated carbon (AC) was chemically activated using sodium hydroxide (NaOH), and polyethyleneimine (PEI) was grafted onto the AC using glutaraldehyde as a cross-linking agent. Then the modified AC was applied to treat water samples containing copper ions (Cu2+). Preparation of AC-NaOH@PEI. The grafted AC was characterized, demonstrating that the specific surface area of material decreased from 959.3 to 556.9 m2/g. The ζ-potential changed from −27.2 to 10.4 mV, and the presence of a distinct flocculation on the surface of the AC was observed via scanning electron microscopy. The results demonstrated that PEI was successfully grafted onto the surface of AC. Furthermore, the adsorption results indicated that the Cu2+ adsorption capacity of AC-NaOH@PEI was greatly enhanced with increasing PEI loading. The adsorption amount of Cu2+ by the grafted AC-NaOH@PEI-200 increased from 20.02 to 47.8 mg/g. In addition, the adsorption of Cu2+ by AC-NaOH@PEI was a pH dependent process. At a pH of 6, the maximum removal rate reached 93%. The adsorption process is better described by the Langmuir and quasi-second order adsorption models, signifying that the adsorption of Cu2+ on AC@PEI consists of monolayer adsorption and chemisorption. After four adsorption-desorption cycles, AC@PEI exhibited high adsorption capacity for Cu2+, indicating that it has good regeneration ability. It is a promising adsorbent material. HIGHLIGHTS Activated carbon modified with glutaraldehyde cross-linked polyethyleneimine was successfully prepared.; The adsorption of copper ions by activated carbon increased from 20.04 mg/g to 47.8 mg/g.; After four times of elution, the removal rate of copper ions could reach 84%.; The adsorption process uses the chelation of copper ions by the amino group in the polyethyleneimine grafted onto the surface of the activated carbon.;